Escherichia coli enterotoxin: stimulation of adenylate cyclase in broken-cell preparations. - Dorner, F (Infect Immun, 1975)
The enterotoxin from cell-free filtrates of the enteropathogenic Escherichia coli strain P-263 was found to stimulate adenylate cyclase activity in broken-cell preparations from myocardial tissue. Particulate and detergent-solubilized fractions from cat heart were incubated with enterotoxin and assayed for adenylate cyclase activity. Adenylate cyclase activity was stimulated by enterotoxin; the extent of stimulation was proportional to the concentration of enterotoxin. The data demonstrate that stimulation of enterotoxin-sensitive adenylate cyclase in this system provides a sensitive in vitro assay, either as an accurate measure of enterotoxin concentration or as an assay for antitoxic titers in sera. A parallel comparison showed that stimulation of fluid production in rabbit intestinal loops by enterotoxin was less sensitive.